Energy management and control for grid connected hybrid energy storage system under different operating modes - Manandhar, Ujjal (2020)
DC-coupled microgrids are simple as they do not require any synchronization when integrating different distributed energy generations. However, the control and energy management strategy between the renewable energy sources and the energy storages under different operating modes is a challenging task. In this paper, a new energy management scheme is proposed for the grid connected hybrid energy storage with the battery and the supercapacitor under different operating modes. The main advantages of the proposed energy management scheme are effective power sharing between the different energy storage systems, faster dc link voltage regulation to generation and load disturbances, dynamic power sharing between the battery and the grid based on the battery state of charge, reduced rate of charge/discharge of battery current during steady state and transient power fluctuations, improved power quality features in ac grid and seamless mode transitions. The effectiveness of the proposed method is validated by both simulation and experimental studies.